The Role of King Pan on Yao Food：Traditions Identity and Guidelines for Promoting Cultural Tourism in Jinxiu - Cai, Rongxiang; Champadaeng, Sitthisak (Journal of Roi Kaensarn Academi, 2024)
In the background of integrated development of culture and tourism, the Yao food of Jinxiu, deeply influenced by the King Pan belief, has demonstrated different cultural values for traditional identity and cultural tourism. This research aims to study: 1. The role of King Pan on Yao food in Jinxiu; 2. The traditional identity of Jinxiu Yao ethnic group and guidelines for promoting cultural tourism. The methodology was as follows: 1. Adopted a qualitative research method; 2. The research tools included literature survey, observation, and interviews; as a research, 2 key informants, 10 casual inforinants and 5 general informants were selected as research sample; 3. Collected data on culture customs of food, cultural performances, cultural identity of Yao, etc, through field work and literature survey; 4. Structural-functional Theory, Cultural Ecology Theory Cultural Diffusion Theory, traditions identity concepts and cultural tourism concepts were used to analyse the research data; research analysis on problems, reasons, suggestions, and tourist experience of the development of Yao cultural tourism, etc; 5. Descriptive analysis methods were used to present the research results. The research results found that: 1. The cultural taboo against eating dog meat and the folk performance of making glutinous rice cake reflected the traditional identification of the Jinxiu Yao people with King Pan from both positive and negative aspects; 2. Jinxiu used the symbol of King Pan on Yao food to develop cultural tourism, but there were some problems in the process of developing cultural tourism resources; These problems included the problems of attracting folk performances, cultural interpretation, and cultural brand dissemination. Through analyzing the reasons, the following guiding suggestions are proposed: strengthening talent introduction, cultural identity, cultural dissemination, cultural research and application, innovating Yao food culture, and strengthening the development of culture tourism resources of Yao food. In conclusion, the prohibition of eating dog meat and the folk performances of making rice cakes are a manifestation of the traditional identity of the Jinxiu Yao people, reflecting their belief in King Pan. It is worth noting that traditional identity has two manifestations: positive and negative. The cultural taboo of the prohibition of eating dog meat is a negative manifestation of the traditional identity of the Yao ethnic group of Jinxiu, while the folk performance of making glutinous rice cake is a positive manifestation of the traditional identity of the Yao ethnic group of Jinxiu, and plays a certain role in cultural tourism.